The cosmological constant and domain walls in orientifold field theories and gluodynamics - Adi Armoni (Nuclear Physics B, 2003)
We discuss domain walls and vacuum energy density (cosmological constant) in N=1 gluodynamics and in non-supersymmetric large N orientifold field theories which have been recently shown to be planar equivalent (in the boson sector) to N=1 gluodynamics. A relation between the vanishing force between two parallel walls and vanishing cosmological constant is pointed out. This relation may explain why the cosmological constant vanishes in the orientifold field theory at leading order although the hadronic spectrum of this theory does not contain fermions in the limit N-->infinity. The cancellation is among even and odd parity bosonic contributions, due to NS-NS and R-R cancellations in the annulus amplitude of the underlying string theory. We use the open-closed string channel duality to describe interaction between the domain walls which is interpreted as the exchange of composite ``dilatons'' and ``axions'' coupled to the walls. Finally, we study some planar equivalent pairs in which both theories in the parent-daughter pair are